International intervention and the Arab uprisings. (c2015) - Kabbara, Khaled (2016)
Should every Human Rights violation lead to intervention? What are the major roles playing factors prompting the decision of intervention in the internal affairs of states? This thesis probes into subject matters on international intervention practices, causes and motives by studying the cases of Libya, Syria and Bahrain, and hence, analyzes each of the situations while basing the arguments on the Responsibility to Protect (R2P) and Keneth Watlz's analysis of international affairs and intervention (representing the neorealist approach). Despite existing similarities between each of the presented cases – especially in terms of human rights violations – the international community's’ reaction and intervention implemented carried different nuances and forms. This thesis will argue that nowadays international military intervention can only occur when it's justified; whether in terms of human rights violations and/or through projecting the threat the situation creates as a global concern. Furthermore, it will demonstrate that not every peace threatening situation where human rights are being violated should result in a direct military intervention. In this respect, it discusses the prime reason which is mainly because states' interests continue to influence its actions, especially when deciding on how to respond to certain situations, whether to intervene militarily in the domestic affairs of states - in pursuit of preserving human rights and international peace and stability- or not.